2015
DOI: 10.1186/s12936-015-0808-y
|View full text |Cite
|
Sign up to set email alerts
|

A molecular survey of acute febrile illnesses reveals Plasmodium vivax infections in Kedougou, southeastern Senegal

Abstract: BackgroundControl efforts towards malaria due to Plasmodium falciparum significantly decreased the incidence of the disease in many endemic countries including Senegal. Surprisingly, in Kedougou (southeastern Senegal) P. falciparum malaria remains highly prevalent and the relative contribution of other Plasmodium species to the global malaria burden is very poorly documented, partly due to the low sensitivity of routine diagnostic tools. Molecular methods offer better estimate of circulating Plasmodium species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 35 publications
1
46
2
Order By: Relevance
“…Both P. ovale (n = 4) and P. malariae (n = 3) were identified from among the 288 RDT-negative samples (Table 1). Although previous reports [7] indicate P. vivax infections in this region, in this study population there were no samples positive for P. vivax. …”
Section: Resultscontrasting
confidence: 72%
See 2 more Smart Citations
“…Both P. ovale (n = 4) and P. malariae (n = 3) were identified from among the 288 RDT-negative samples (Table 1). Although previous reports [7] indicate P. vivax infections in this region, in this study population there were no samples positive for P. vivax. …”
Section: Resultscontrasting
confidence: 72%
“…Kédougou, in southeastern Sénégal, is a region that borders Mali and Guinea with relatively high transmission, as indicated by entomological inoculation rates (EIRs) of 100–200 [9, 10]. Recent reports have identified P. vivax malaria in Kédougou [7]. Although P. vivax was not observed in the population assessed in the current study, P. ovale wallikeri, P. ovale curtisi, and P. malariae were identified, none of which are tested for by the current RDT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the situation is particularly worrying in the Southeastern part of the country due to limited impact of applied preventive and control measures [2]. In Kedougou, a region situated in southeastern Senegal, malaria due to Plasmodium falciparum remains highly prevalent [2, 3], particularly during the transmission season that coincides with the rainy season from July to November. In 2014, the National Malaria Control Program (NMCP) reported 25.55% of malaria incidence of which 2.73% turned into severe disease [2].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, accurate diagnosis appears to be crucial for the successful treatment of malaria, and molecular approaches by polymerase chain reaction (PCR) diagnostic assays have lately evolved, across the world, as the most sensitive method for this purpose in comparison to the traditional microscopy method [2][3][4][5][6]. In addition, Plasmodium vivax is now capable of not only infecting Africans, who are ordinarily recognized as resistant to malaria infection due to this parasite, but also of causing severe malaria [7]. In this respect, newer studies have reported that Duffy-negative native Cameroonians can also be infected by P. vivax [5,6].…”
mentioning
confidence: 99%